A Descriptive Analysis of Peripheral Arterial Disease: Clinical Profile, Comorbidities, And Management Outcomes - Vinojan, S.; Thananchayan, H.; Niranjan, N. (Kandy Society of Medicine, 2026)
Background: Peripheral Arterial Disease (PAD) presents a significant burden, particularly in patients with multiple comorbidities, highlighting the need for early diagnosis and timely intervention. Objectives: To describe the clinical profile, comorbidities, anatomical distribution, interventions, and outcomes in patients with PAD. Method: A prospective descriptive study of 57 PAD patients admitted to the professorial unit of Teaching Hospital Jaffna. Data were collected from clinical records and BHTs. Results: The mean age was 66 years. Diabetes Mellitus was the most common comorbidity (73.7%, n = 42), followed by hypertension (31.6%, n = 18), ischemic heart disease (19.3%, n = 11), and dyslipidaemia (15.8%, n = 9). Tissue loss is the commonest presentation for Chronic Limb Threatening Ischemia (CLTI). Among 41 patients with imaging data, tibial vessels (46.3%, n = 19) and superficial femoral artery (39%, n=16) were most commonly involved. Iliac (n = 1), combined SFA and tibial (n = 3), and foot arch disease (n = 2) were less frequent. Definitive procedures were performed in 78.9% (n = 45); angioplasty (54.4%, n = 31) was most common, followed by femoral-popliteal bypass (19.3%, n = 11). Others were managed conservatively or with wound care. Outcomes included wound healing in 22.8% (n = 13), healing in progress in 10.5% (n=6), and major amputations in 7% (n = 4). There were 3 deaths (5.3%) due to myocardial infarction. Most others showed clinical improvement. Follow-up revealed 2 defaults, 1 symptomatic improvement, 2 reinterventions, 4 minor amputations (toe/forefoot), 2 recurrent wounds, 1 redo bypass, 1 post-op angioplasty, 1 aneurysm repair, and 1 awaiting bypass. Conclusion: PAD primarily affects elderly diabetics, with CLTI as the commonest presentation. Tibial and femoral arteries were most involved. Angioplasty was the mainstay of treatment. Despite encouraging outcomes, complications emphasize the need for early intervention and structured follow-up.